Kondisi Terumbu Karang di Kawasan Taman Nasional Laut Kepulauan Seribu DKI Jakarta - Drajad Sarwo Seto; Djumanto -; Namastra Probosunu (Universitas Atma Jaya Yogyakarta, 2014)
AbstractThe objective of this research was to determine the condition of coral reefs, namely the percentage of coral covered, species distribution, community structure of coral, and the environmental conditions surround the core zone, protection zone, tourism zone, and residential zone in Kepulauan Seribu Marine National Park DKI Jakarta. The research was conducted from 8 to 16 May, 2013. The data was collected from four zones and each zone was set up into two stations as a point observation, at the depth of 7ï€9 meters. The percentage of coral coverring was calculated by line intercept transect method, coral genera was counted and identified using the belt transect method. Coral data was analyzed qualitatively based on ecological index. The results showed that the coral covering was range from 7.25 to 68.93% as categorized from bad to good condition. The number of coral was found approximately of 5.523 colonies that consisted of 45 genera and 16 families. The most abundance of coral was Porites and Montipora with percentage of 19.7% and 16.69%, respectively. Coral diversity index was ranged from 1.61 to 3.07 as indicated of low to high. Uniformity index was ranged from 0.44 to 0.68, which was the community in stressful to labile situation. Dominance index (D) was ranged from 0.06 to 0.32 showing that coral dominance was absence.Keywords: Coral reef, cover, diversity, Kepulauan SeribuAbstrakPenelitian ini bertujuan mengetahui kondisi terumbu karang yang meliputi persentase tutupan, sebaran, struktur komunitas dan kondisi lingkungan di zona inti, perlindungan, pemanfaatan wisata, dan pemukiman di kawasan Taman Nasional Laut Kepulauan Seribu DKI Jakarta. Penelitian dilaksanakan dari tanggal 8 sampai 16 Mei 2013. Pengambilan data berada pada empat zona pengelolaan dan setiap zona ditetapkan sebanyak dua stasiun pengamatan pada kedalaman 7ï€9 meter. Persentase tutupan karang dihitung dengan metode Line Intercept Transect, genera karang dihitung dan diidentifikasi menggunakan metode Belt Transect. Data jenis karang yang diperoleh dianalisis kualitatif berdasarkan indeks ekologis. Hasil penelitian diperoleh persentase tutupan karang berada pada kisaran 7,25ï€68,93% yang dikategorikan kondisinya buruk hingga baik. Jumlah karang dari seluruh stasiun penelitian sebanyak 5.523 koloni yang terdiri dari 45 genera dan 16 famili. Genus karang yang paling sering dijumpai adalah Porites dan Montipora dengan persentase kelimpahannya masing-masing 19,7% dan 16,69%. Nilai indeks keanekaragaman (Hâ€™) karang berkisar antara 1,61ï€3,07 yang tergolong rendah hingga tinggi. Indeks keseragaman berkisar 0,44ï€0,68 yang berarti komunitas dalam keadaan tertekan hingga labil. Nilai indeks dominansi (D) berkisar 0,06ï€0,32 yang menunjukkan dominansi karang tertentu tergolong rendah.Kata kunci: Tutupan, terumbu karang, keragaman, Kepulauan Seribu